Improved method for preparing Ni(II) complex of (S)-tyrosine Schiff base and its use in the automated synthesis of O-(2′-[18F]fluoroethyl)-l-tyrosine using solid-phase extraction purification. (September 2017) - Lakshminarayanan, N.; Kumar, Amit; Roy, Sushant; Pawar, Yogita; Chaudhari, Pradip; Rajan, M.G.R.
Abstract: O-(2′-[ 18 F]fluoroethyl)-l -tyrosine is reportedly suitable for PET-imaging of brain tumours. We report here the synthesis of Ni(II)-complex of Schiff's base (S)-[N-2-(N′-benzylprolyl)amino]-benzophenone, ((S)BPB) and alkylatedl -tyrosine precursor, Ni(II)-(S)-BPB-l -Tyr-O-CH2 -CH2 -OTs by an improved method. A fully-automated radio-synthesis including non-HPLC purification was developed with a radio-chemical yield of 24.6 ± 2% in 70 ± 2 min (n = 5). Radiochemical and enantiomeric purity was > 98% and 94% respectively. Bio-distribution and micro-PET studies in C57BL/6 mice bearing B16F10 melanoma showed tumor to brain ratio of 3.36 and 3.62 respectively at 60 min post-injection. Highlights: Improved method for synthesis of Ni(II)-(S)-BPB-l -Tyr-O-CH2-CH2-OTs precursor for [ 18 F]FET. Automated radio-synthesis of [ 18 F]FET including SPE purification with 24.6% yield. Radiochemical purity > 98% and enantiometric purity > 94%. Micro-PET studies in C57BL/6 mice with B16F10 melanoma showed tumor to brain ratio of 3.62 at 60 min.